AR Application Design Requirements for Technical Education - Litecká, Juliána; Mitaľová, Zuzana (The University of Rzeszów Publishing House, 2024)
We cannot question the importance of technical education at the present time. Each education has its own specifics, which must be considered during scientific and research activities. The paper deals with the AR application design in education. Within this contribution, we are based on the characteristics of augmented reality and the possibilities of developing applications for education, which relate to the Cognitive Theory of Multimedia Learning and our experience with the possibilities of creating applications in augmented reality. Based on this, in the contribution we defined five key areas (appearance, functionality, content, cognitive effectivity and sharing, compatibility and connectivity) of requirements for the design of AR applications with the specification of cognitive effectivity for technical education.
Keywords: augmented reality; technical education; AR application; design requirements